Pengaruh Motivasi terhadap Produktivitas Kerja Karyawan PT. Telkom Tbk Cabang Makassar - Nurnaningsih Nurnaningsih; Ridwan Tabe (IAIN Manado, 2019)
Effects of Motivation on Work Productivity of PT. Telkom Tbk Employees in Makassar Branch. The purpose of this study is 1) To determine the effect of employee motivation (External and Internal) on Employee Productivity at PT. Makassar Branch Telkom, 2) To find out which motivation is more dominant in influencing employee work productivity at PT. Telkom Makassar Branch. Data used in this study are primary and secondary data. Population in this study are all employees who work at PT. Telkom Tbk Makassar Branch, amounting to 540 people. Determination of samples using a simple random sampling technique which if the number of research subjects is less than 100, it is better to take all but if the subject is large then only 10% is taken so the total population taken is 54 people. The analytical method used in this study is multiple linear regression analysis using SPSS. The results showed that: 1) External Motivation in PT. Telkom companies had a significant influence on performance productivity based on employee perceptions, 2) From the results of the analysis, the results showed that external motivation (Working Conditions, Good Bosses, Financial and Social Guarantees) had an effect towards the productivity of the company. While the analysis obtained from internal motivation (Exciting Work, Challenging Work, and Attractive Work) has an influence on productivity. Thus, the proposed hypothesis is proven, 3) External and internal motivation has a simultaneous effect on employee performance. This is evidenced by the coefficient of determination test, which is equal to 47% of employee performance is influenced by variations in the two variables used in the study, the remaining 53% is influenced by other factors, 4) External motivation is more dominantly influencing employee performance this is evidenced by external motivation regression coefficient greater than internal motivation, 5) Internal motivation is the most dominant influence on productivity is good communication between employees and supervisors of internal motivation is the work performance that is owned based on the research conducted.